Longing, weakness, and temptation : from myth to artistic creations - Avsenik Nabergoj, Irena, 1969- (Cambridge Scholars Pub., 2009)
The themes of longing, weakness and temptation are relevant to every human and are interwoven with all fundamental ideals and values of the created, rational being. Temptation is all the more dramatic, the broader the perspective of recognition, the power of human longing and the sense of the difference between good and evil. This book is a summary of a study which compares and contrasts Slovenian and European literary works created under the influence of biblical source texts (Adam and Eve ...